Mulching improved soil fertility, plant growth and productivity, and postharvest deficit irrigation reduced water use in sweet cherry orchards in a semi-arid region. Issue 8 (3rd July 2023) - Gebretsadikan, Tirhas; Munro, Paige; Forge, Tom A.; Jones, Melanie D.; Nelson, Louise M.
ABSTRACT: In the Okanagan Valley, sweet cherry production has expanded to higher latitudes due to climate change, but the availability of irrigation water is limited in this semi-arid region. Postharvest deficit irrigation (PDI) and organic mulches can reduce water use in orchards, but their interactive effects on soil fertility, water relations, and crop performance in new orchard environments are unknown. In a randomized block split-plot design, full irrigation (100%) or PDI (72–76% of full irrigation) was applied to the main plots, and mulches (compost, woodchips, bare) were subplots at three sites. Compost increased soil organic matter, nutrients, pH, and electrical conductivity over three seasons at all sites. Woodchips increased tree growth and foliar P and Mn, while compost increased some fruit quality attributes, and foliar P compared to bare soil. Relative to full, PDI saved 24–28% irrigation water after harvest per season at each site without affecting soil moisture and chemical properties, stem water potential, or crop performance, or interacting with mulch effects. These results suggest that in this semi-arid cherry growing region mulches are a promising strategy to maintain soil moisture and improve soil fertility and crop performance, and PDI can reduce water use after harvest without affecting commercial production.